EVALUASI PENERAPAN STANDAR PELAYANAN KEFARMASIAN PADA PUSKESMAS DI KOTA KUPANG PERIODE MARET SAMPAI DENGAN MEI TAHUN 2023 - Panduwiguna, Ivans; Mbau, Yansen Marthen; Rahman, Reza Ismail Abdul (As-Syifaa Jurnal Farmasi, 2024)
Pharmaceutical services at community health centres (puskesmas) are integral to the implementation of health efforts in advancing the quality of health services and improving the quality of life of patients, which are carried out by pharmacists directly. This study was conducted at community health centres in the Kupang City area because there has been no previous research related to the evaluation of pharmaceutical services. The purpose of this study was to determine the suitability of the implementation of pharmaceutical service standards at community health centres in the Kupang City area with Permenkes No. 74 of 2016 as a guideline in performing pharmaceutical services at community health centres. This study used an observational method with a descriptive approach using a checklist sheet. This study was conducted in the period March 2023-May 2023. The study sample was 11 respondents from Puskesmas Alak, Puskesmas Bakunase, Puskesmas Kupang Kota, Puskesmas Manutapen, Puskesmas Naioni, Puskesmas Oebobo, Puskesmas Oepoi, Puskesmas Oesapa, Puskesmas Pasir Panjang, Puskesmas Penfui, Puskesmas Sikumana. The results showed that the suitability of pharmaceutical services at Puskesmas in the Kupang City area was in accordance with Permenkes No. 74 of 2016 with the results of the checklist sheet getting an average of 78% with a good category.